2020
DOI: 10.1007/978-3-030-44914-8_23
|View full text |Cite
|
Sign up to set email alerts
|

ARMv8-A System Semantics: Instruction Fetch in Relaxed Architectures

Abstract: Computing relies on architecture specifications to decouple hardware and software development. Historically these have been prose documents, with all the problems that entails, but research over the last ten years has developed rigorous and executable-as-test-oracle specifications of mainstream architecture instruction sets and "user-mode" concurrency, clarifying architectures and bringing them into the scope of programming-language semantics and verification. However, the system semantics, of instruction-fetc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…By handling the full authoritative Armv8-A ISA, we automatically support litmus tests that use arbitrary instructions, and we enable research on systems concurrency, with high confidence that the ISA follows the vendor specification. We demonstrate this by applying our tool to the model and examples for self-modifying code by Simner et al [27], and our integration has also identified several places where the ISA specification needs modifications to correctly give the intended behaviour in a concurrent setting, e.g. to remove or enforce additional ordering.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…By handling the full authoritative Armv8-A ISA, we automatically support litmus tests that use arbitrary instructions, and we enable research on systems concurrency, with high confidence that the ISA follows the vendor specification. We demonstrate this by applying our tool to the model and examples for self-modifying code by Simner et al [27], and our integration has also identified several places where the ISA specification needs modifications to correctly give the intended behaviour in a concurrent setting, e.g. to remove or enforce additional ordering.…”
Section: Introductionmentioning
confidence: 84%
“…For the instruction-semantics part of such a tool, the most direct approach would be to translate the ISA semantics (for the instructions that occur in a litmus test) directly into SMT and combine that with the axiomaticmodel constraints, roughly along the lines of Alglave et al [3]. That approach was followed by Simner et al [27], who compiled Sail directly into SMT to test an axiomatic model for instruction-fetch tests, but using a small handwritten Arm fragment, rather than the full Sail model derived from the Arm-internal model. The problem with this direct approach is one of scale: as one covers more of the Arm semantics, the resulting SMT problem simply becomes too large to be practicable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researches have been made to improve the ARM/Thumb instruction set architecture [5]- [27]. However, little attentions have been paid to the extension of specific modes such as addressing mode and sign/zero extension for the ARM instruction architectures.…”
Section: Introductionmentioning
confidence: 99%